Between Prohibition and Permissibility of Islamic Art: An Application of Ma’na-Cum-Maghza Approach on Hadiths of Music, Painting and Dance - Nur Laili Nabilah Nazahah Najiyah; Dadi Nurhaedi (UIN Sunan Kalijaga Yogyakarta, 2022)
The problem of music, painting (drawing), and dance in Islam still has differences of opinion regarding the banning of the three. This variety of opinions arises based on verses from the Qur`an and hadith to strengthen their respective arguments. This study reveals how the hadiths about art could be understood and contextualized using the Ma’na-Cum-Maghza Sahiron approach, as well as their relevance in the study of hadith. This qualitative study uses sociological and historical approaches, and the data obtained are analyzed using explanatory analysis techniques. There are two findings in this study: first, in the hadiths of music, painting (drawing) and dance, there is no message that implies a prohibition on these three arts. The hadiths appeared and only took effect at that time or according to the context of certain events behind the emergence of these hadiths. Second, in the current context, the meaning and application of these hadiths must be relevant to the times by paying attention to human interests and needs. If these arts turn out to have a positive impact on human life, then it is possible that these arts can be applied. In the context of hadith studies, the combination of studies of discussions related to art and the application of Ma’na-Cum-Maghza approach is useful for understanding all three in one study so that the understanding of them becomes more integral-comprehensive.